MUSCA SPP. FLIES INFESTATION ON A PIG FARM IN THE CITY OF DENPASAR - Maria Fatima Suzana das Dores Sanches; I Made Dwinata; Ida Bagus Made Oka (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
The role of flies in spreading disease is as a mechanical vector and a biological vector. As a mechanical vector flies carry pathogenic agents through their limbs. The fly's body has many hairs, especially on its legs. The hairs on the legs contain a kind of adhesive liquid so that small objects stick easily. Diseases transmitted by flies depend on the species. This study aims to determine the fluctuations and differences in the number of Musca spp. in a different environment on a pig farm in Denpasar City. This type of research is an observational study. The sample for this study were Musca sp. flies in two pig farms in Denpasar City. Samples were taken every day for 4 weeks at 09.00 – 14.00. Data analysis used the Wilcoxon test. The results showed that the Musca spp. found in pig farms in Ubung Kaja Village, North Denpasar, as many as 358 pigs and in Sidakarya Village, South Denpasar, as many as 981 pigs. The population of flies on pig farms in Ubung Kaja Village, North Denpasar and Sidakarya Village, South Denpasar, during 4 weeks of observation, fluctuated with the highest decrease in the 4th week and while the increase occurred in the 2nd week in North Denpasar, while in South Denpasar there was an increase in the 2nd week. up to 3. Based on the results of the study, it can be concluded that the population of flies on pig farms in Ubung Kaja Village, North Denpasar and Sidakarya Village, South Denpasar, during 4 weeks of observation, fluctuated with an increase occurring in the 3rd week in North Denpasar, while in South Denpasar there was an increase in the 2nd to 2nd week. 3. There is no difference in the number of Musca spp. in a different environment on a pig farm in Denpasar City. From these results, it can be suggested that pig farms should further improve environmental sanitation in their pens and surroundings by disposing of waste in properly managed bins and implementing good biosecurity. The research can be continued by increasing the number of places studied at different seasons so that the fluctuations of flies in the rainy and dry seasons can be determined.